A rewriting of Pygmalion from a female (and feminist) perspective: «Galatea» by Madeline Miller. - Chiara Valenzano (Griseldaonline)
In the context of contemporary publishing, which has witnessed the considerable success of the genre of female mythological retelling, Madeline Miller is a notable figure. Miller is an American author who has already published two novels and two short stories dedicated to rewriting episodes from classical mythology. The short story entitled Galatea represents a noteworthy reinterpretation of Ovid’s tale of Pygmalion from a feminist perspective. In contrast to the original narrative, which celebrates the power of art and the artist, Galatea becomes a narrative of violent love and possession. In this reimagining, the woman is positioned as subaltern and confined by her husband. The myth thus provides a foundation for elucidating the pervasively contemporary phenomenon of domestic violence. Galatea’s arduous pursuit of autonomy and freedom prompts the reader to reflect on the enduring relevance of classical narratives, despite their tragic persistence.